Concept of “Uzbek Intelligentsia” in historical-cultural and socio-philosophical discourse - Mamura, Burkhanova (Goodwood Publishing, 2024)
Purpose: This study explores the evolution of the concept of “Uzbek intelligentsia” across historical epochs from Jadidist reformism and Soviet ideological structuring to post-independence digital civic engagement. Research methodology: The research adopts a multi-layered qualitative method combining cultural-historical analysis, conceptual mapping, and critical discourse analysis using NVivo software. Results: The study identifies intelligentsia as a dynamic and adaptive identity shaped by socio-political transformations. Key conceptual nodes such as marifatchi and xalqparvarlik persist across time, highlighting continuity in moral-intellectual responsibility. Conclusions: The Uzbek intelligentsia is not a static class but a fluid identity dialectically formed through interactions with shifting historical conditions and evolving societal questions. Limitations: The study is limited to qualitative interpretation, lacking quantitative generalization of public perceptions across broader demographics. Contribution: This work offers a theoretical framework for analyzing intelligentsia as an ethical, socio-historical process bridging past traditions with present digital reform.